The toll of household water insecurity on health and human biology: Current understandings and future directions - Rosinger, Asher Y.; Young, Sera L. (Wiley interdisciplinary reviews. Water, 2020)
Water is imperative for nutrition and health, economic productivity, and political stability; it also holds cultural and symbolic meanings and functions. Household water insecurity is an emerging construct that captures lived experiences with water access, use, and acceptability. Although the plausibility of household water insecurity to “get under the skin” and shape human biology is high, these relationships have not been systematically investigated. Therefore, in this article, we set out to examine how household water insecurity and allied concepts affect health and human biology throughout the life course. We first lay out the various ways that water insecurity can act as a deleterious exposure, that is, through problematic quality, excess, and shortage. Next, we posit how water insecurity directly shapes human biology, as well as indirectly, via psychosocial stress precipitating cortisol exposure, with potential intergenerational effects. We highlight a range of established and plausible biological consequences using evidence from human and animal model studies. These include diarrheal prevalence, dehydration, stunting, food insecurity, gut microbiome alteration, malnutrition, psychosocial stress, adverse birth outcomes, lower cognitive function and performance, hypertension, and chronic kidney disease. We also discuss the mechanisms by which household water insecurity may shape human biology across the life course; however, these pathways are just beginning to be understood. Longitudinal studies that simultaneously quantify household water insecurity and biological outcomes using comparable metrics in diverse environments and across generations will provide necessary evidence to establish causal relationships. Given the current global water crisis and its potential health consequences, such studies are urgently needed. This article is categorized under: Engineering Water > Water, Health, and Sanitation Science of Water > Water Quality Plausible and observed key effects of water insecurity on human biology and health by life stage, with potential intergenerational relationships.